2020
DOI: 10.1108/mip-01-2020-0033
|View full text |Cite
|
Sign up to set email alerts
|

Do experience and engagement matter to millennial consumers?

Abstract: PurposeThe purpose of this research is to examine the effect of certain dimensions of brand experience (sensory, behavioural, affective and intellectual) on millennial consumers' engagement.Design/methodology/approachData were collected using the central location intercept method from 443 millennial consumers (aged between 18 and 35 years) of fashion apparel. Structure equation modelling was used for the analysis.FindingsResults showed that all dimensions of brand experience (namely, sensory, behavioural, affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
17

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 44 publications
2
17
0
17
Order By: Relevance
“…As customer experience has a positive impact on loyalty, its outcomes present several benefits for the company such as: trust, customer loyalty, increased commitment, a positive word-of-mouth [39,40,72]. The perception of a relevant customer experience could lead to a greater commitment to the company, which is reflected in customer loyalty [43,106]. Studies on customers experience with online retail applications have indicated a positive influence of cognitive and affective experience on customer loyalty [57,107].…”
Section: Hypothesis 4 (H4) Assurance Is Positively Associated With Customer Experiencementioning
confidence: 99%
“…As customer experience has a positive impact on loyalty, its outcomes present several benefits for the company such as: trust, customer loyalty, increased commitment, a positive word-of-mouth [39,40,72]. The perception of a relevant customer experience could lead to a greater commitment to the company, which is reflected in customer loyalty [43,106]. Studies on customers experience with online retail applications have indicated a positive influence of cognitive and affective experience on customer loyalty [57,107].…”
Section: Hypothesis 4 (H4) Assurance Is Positively Associated With Customer Experiencementioning
confidence: 99%
“…Zajímají je různé věci, např. jaké je jejich očekávání ohledně vzdělání (Licite a Janmere, 2017), zda je pro ně důležitá zkušenost a závazek (Khan et al, 2021) nebo jaké jsou jejich vztahy a efektivita na pracovišti (např. Cheng et al, 2018, Alonso-Almeida a Llach, 2019, Sao a Tolani, 2018.…”
Section: Generaceunclassified
“…PBA is defined as consumers' perceptions of a brand's authenticity in terms of quality commitment, sincerity and heritage (Napoli et al, 2014). Consumers today are confronted with the ever-growing commercialization of products, services and the globalization of markets (Morhart et al, 2015;Khan et al, 2021). The excessive proliferation of brands and the growth and maintenance of consumer-brand relationships are two critical strategic challenges in brand management (Oh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%